ULTRASONOGRAPHIC DIAGNOSIS AND TREATMENT OF HYDROMETRA IN JAMNAPARI GOATS - JAYAKUMAR, C; SUDHA, G; KANTHARAJ, S; LAKSHMIKANTH, k (The Indian Journal of Animal Reproduction, 2016)
The clinical diagnosis of hydrometra in two Jamnapari goats was carried out by ultrasonography and thecases were successfully treated with a single dose of PGF2α.
Keywords: Goat; Hydrometra; PGF2α